Diseño de una maquina laminadora de trigo y agregados para la elaboración de tortillas - Amaro Gutierrez, Seimer (2018)
The design of this laminating machine has a nutritional objective, since its final product would benefit a large segment of the population due to the ingredients of the dough that we could mix like wheat flour, soy, maca, quinoa, sweet potato, wheat, etc., which would help improve the nutrition, health and quality of life of consumers. The project focuses on the design of the main elements of a laminating machine: laminating cylinders, cutter cylinder and conveyor belt. Alternatives are proposed in the design of laminating cylinders, and of a laminating cylinder with an innovation. Two cutter profiles are arranged so that for each rotation of the laminating cylinder there are two sheets of the requested material, in addition, for each revolution of the laminating cylinder three rotations of the cutter cylinder will be given, making the proposed model more efficient. After the design process we obtain that the laminating cylinders must have a diameter of 6 inches, described in the ASTM A312. It was possible to design the cutter cylinder with the calculations contemplated in this material obtaining a 2 1/2 inch diameter tube, schedule 80, described in ASTM A312. The volumetric capacity of the conveyor belt of 0.177 m3 / h and the transport capacity of 0.133 ton / h was determined. The project responds to the requirement to produce 3600 tortillas / h. in addition to a required capacity of 0.324 ton / h based on pre-established conditions and calculations described in the present study.